An exploration of the ballistic resistance of multilayer graphene polymer composites. (February 2017) - O'Masta, M.R.; Russell, B.P.; Deshpande, V.S.
Abstract: The response of multilayer graphene/polyvinyl alcohol (MLG/PVA) films were studied under quasi-static (Q.S.) and dynamic edge-clamped transverse loading. The 10 μm thick films, reinforced by ∼35 vol.% MLG and measuring 85 mm square were fabricated by liquid exfoliation of the graphene followed by filtration of the MLG/PVA dispersion. The responses of the MLG/PVA films were compared with those of equal areal mass films of pure PVA and aluminum. The moderately conductive (∼10 −2 S cm −1 ) MLG/PVA films had a Young's modulus approximately twice that of PVA and a low strain rate (10 −3 s −1 ) peak strength that was about 50% higher. Moreover, while the MLG/PVA films had a tensile strength lower than the Al films, they had a higher load carrying capacity compared to the Al films and were stiffer than the PVA films under Q.S. transverse loading. The ballistic limit of the MLG/PVA films was ∼50% higher than the Al films but the higher ductility of the parent PVA resulted in the pure PVA films having a higher ballistic resistance. The ballistic resistance of the MLG/PVA is well predicted by a membrane stretching analysis and this enables us to present an outlook on the ballistic resistance potential of graphene/PVA composites comprising aligned large flakes. Graphical abstract: